A T-shaped partial ground microstrip patch antenna based UHF sensor for partial discharge detection - Azhar N.A.; Aripin N.M.; Hock G.C.; Ferdous N.; Hamidah S. (Institute of Advanced Engineering and Science, 2023)
Continuous partial discharge (PD) monitoring and early PD detection is important in making sure the necessary preventative measures can be taken accordingly. This paper proposed a T-shaped partial ground microstrip patch antenna that is able to detect PD signal within the UHF range. The antenna was designed and simulated using CST Microwave Studio. The antenna was then fabricated using FR4 substrate material and tested for reception test. The simulation results and the analysis from the fabricated antenna confirmed that the proposed antenna able to detect PD signal at UHF range (specifically at about 500 MHz) and fulfilled the design requirements in terms of the return loss, VSWR, bandwidth and gain. Reception test had confirmed that the proposed antenna was able to detect PD signals that are located at maximum distance, ranges from 37 cm to 70 cm (depending on the PD signal strength). The proposed antenna also had succesfully detected PD occurances at 300 MHz to 700 MHz. In conclusion, the proposed T-shaped partial ground microstrip patch antenna had been successfully designed and able to detect PD signal emitted in the UHF range. Copyright 2020 Institute of Advanced Engineering and Science. All rights reserved.